2021
DOI: 10.1177/17455065211067073
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopia’s commitment towards achieving sustainable development goal on reduction of maternal mortality: There is a long way to go

Abstract: Maternal mortality reduction has been recognized as a key healthcare problem that requires prioritizing in addressing. In 2015, the United Nations has set Sustainable Development Goals to reduce global maternal mortality ratio to 70 per 100,000 live births by 2030. Ethiopia as a member country has been working to achieve this Sustainable Development Goals target for the last decades. In this article, we discussed Ethiopia’s commitment towards achieving Sustainable Development Goals in maternal mortality. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…To address this and other global development gaps, a new global strategy has been set in 2015 called the Sustainable Development Goal (SDG) which was aimed to replace the Millennium Development Goal (MDGs) that culminated in 2015. The SDG considers maternal mortality as one of the global health indicators and sets a target to reduce global maternal mortality to fewer than 70 deaths per 100,000 live births by 2030 [3].…”
Section: Introductionmentioning
confidence: 99%
“…To address this and other global development gaps, a new global strategy has been set in 2015 called the Sustainable Development Goal (SDG) which was aimed to replace the Millennium Development Goal (MDGs) that culminated in 2015. The SDG considers maternal mortality as one of the global health indicators and sets a target to reduce global maternal mortality to fewer than 70 deaths per 100,000 live births by 2030 [3].…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted in Indonesia, Brazil, Saudi Arabia, and Malaysia found that Apgar score, gestational age, birth weight, gender, premature rupture of membrane, prolonged rupture of membrane, Chorioamnionitis, antenatal care, and infection during pregnancy were factors associated with early onset neonatal sepsis [ [13] , [14] , [15] , [16] ]. To achieve the Sustainable Development Goal (SDG), Ethiopia is putting more effort to reduce neonatal mortality to less than 12 deaths per 1000 live births [ 17 ]. For instance, expanding health-care facilities in various parts of the country and training healthcare personnel [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates from international agencies may differ from official national statistics. Indeed, a study in Ethiopia showed that maternal mortality data provided by international agencies underestimated maternal mortality: 401 versus 412 per 100,000 [36]. -Deaths registration and recording of the cause of death as a part of the Vital statistics system are deficient in many countries of Africa, and in 2015 the regional average completeness rate of death registration was only 34.6% [37].…”
Section: Discussionmentioning
confidence: 99%